Gaun “Divine Armor of Grace” Dengan Bustier Resin: Penciptaan dan Uji Kelayakan Estetika Busana Couture - Nimas Ayu Pawestri Atmaja; Adhi Kusumastuti (LPPM Institut Pendidikan Nusantara Global, 2026)
This study employs a practice-based research approach that emphasizes the process of design and creative practice as a primary source of knowledge production. The research focuses on the creation of a conceptual couture evening gown entitled Divine Armor of Grace, which represents symbols of protection, strength, and elegance as expressions of feminine identity. The design explores the use of a resin bustier as a non-conventional material combined with textile elements to create a sculptural yet aesthetic silhouette, while integrating batik as a representation of local cultural values. Product feasibility was evaluated through expert validation involving three expert validators, consisting of two fashion design experts and one academic expert in fashion studies. The evaluation covered six aspects, namely design, sizing accuracy, sewing technique, aesthetics, garment performance, and uniqueness. Data were collected through observation and product evaluation instruments and analyzed using descriptive Persentase analysis. The results indicate that the Divine Armor of Grace gown achieved feasibility scores within the range of 81.25–100%, categorized as Highly feasible, with the highest scores obtained in design, aesthetics, performance, and uniqueness, while sewing technique showed comparatively lower scores indicating areas for further refinement. These findings confirm that the Divine Armor of Grace gown is highly feasible as a conceptual couture work developed through a practice-based research approach and contributes to the exploration of innovative materials in contemporary fashion design.